2009
DOI: 10.1645/ge-1804.1
|View full text |Cite
|
Sign up to set email alerts
|

Redescription of Rhadinorhynchus ornatus (Acanthocephala: Rhadinorhynchidae) from Skipjack Tuna, Katsuwonus pelamis, Collected in the Pacific Ocean off South America, with Special Reference to New Morphological Features

Abstract: Adults of Rhadinorhynchus ornatus Van Cleave, 1918 were collected from the small intestine of skipjack tuna, Katsuwonus pelamis (Linnaeus), in the high seas of the Pacific Ocean off the west coast of South America (new parasite locality record) and described using optical microscopy and a scanning electron microscope (SEM). Our specimens were somewhat comparable to those described from North America and Japan, but had more trunk spines. Definitive differences between the length and thickness of each of the dor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 25 publications
0
31
0
Order By: Relevance
“…In Tenuiproboscis sp (Sanil et al 2011) observed a progressively decreasing size of hooks from anterior to posterior region, but the posterior most row of spines was larger. As in most acanthocephalan species, hook surface is smooth in E. veli in contrast to surface striations in Porrorchis indicus (Abd-El-Moaty and Taeleb, 2011), Dentitruneus truttae (Dezfuli et al 2008) and Rhadinorhynchus ornatus (Amin et al 2009). Dezfuli et al (2008) speculated that the striations may help effective attachment to the host intestinal wall.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In Tenuiproboscis sp (Sanil et al 2011) observed a progressively decreasing size of hooks from anterior to posterior region, but the posterior most row of spines was larger. As in most acanthocephalan species, hook surface is smooth in E. veli in contrast to surface striations in Porrorchis indicus (Abd-El-Moaty and Taeleb, 2011), Dentitruneus truttae (Dezfuli et al 2008) and Rhadinorhynchus ornatus (Amin et al 2009). Dezfuli et al (2008) speculated that the striations may help effective attachment to the host intestinal wall.…”
Section: Discussionmentioning
confidence: 85%
“…The trunk epidermis in E. veli has micropores and microtriches increasing the surface area of nutrient absorption. There are both micropores and microtriches in some acanthocephalans (Amin et al 2009). Microtrichus are highly specialised microvilli covering the entire surface of the tegument of cestodes and some acanthocephalans.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their present reporting in N. dimorphospinus (Eoacanthocephala: Neoechinorhynchidae), ribbed hooks have also been reported in 3 other species in 2 other families of Palaeacanthocephala: Dentitruncus truttae Sinzar, 1955 (Illiosentidae), Rhadinorhynchus ornatus Van Cleave, 1918 (Rhadinorhynchidae), and Leptorhynchoides polycristatus Amin, Heckmann, Halajian, El-Naggar, Tavakol, 2013 (Rhadinorhynchidae). Dezfuli et al (2008) and Amin et al (2009) suggested that such hook striations may provide a more effective attachment to the host's intestine. The striations of the hooks of D. truttae appeared as small dents on the outer periphery of the hooks' outer striped layer (Dezfuli et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…10). These peripheral canals are continuous with canalicular crypts, which appear to constitute a huge increase in external surface area and which are also implicated in nutrient uptake (see Whitfield 1979 andAmin et al 2009 for a discussion of this topic). Accordingly, it would appear that nutrient uptake is similar along the length of the trunk and not variably performed in different regions of the trunk as has been shown for both Acanthocephalus lucii (Müller, 1776) Lühe, 1911, and Acanthocephalus ranae (Schrank, 1788) Lühe, 1911, by Amin et al (2011) and Heckmann et al (2011), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…10). See Amin et al (2009) for implications to differential absorption. The terminal position of the crescent-shaped female gonopore (Fig.…”
Section: Resultsmentioning
confidence: 99%